Analisis Kapasitas Jalan Kawasan Pertokoan Somba Opu Akibat Parkir Pada Badan Jalan - Amalia, Sri Wahyuni; Mallawangeng, Tamrin; Yunus, Ahmad Yauri (Program Studi Teknik Sipil Universitas Bosowa, 2025)
Traffic plays an important role in supporting daily activities and economic growth, especially in Makassar City which experiences an increase in traffic volume of around 3% per year. One of the problems that arises is the limited parking area, especially on Jalan Somba Opu which is a trading center. Parking on the roadside reduces road capacity by 30-40% and worsens congestion, especially with the 30° diagonal parking model which leaves an effective road width of only 3 meters. This study analyzes the impact of parking on the roadside on traffic performance, showing that road capacity decreased from 1,750 smp/hour to 1,333 smp/hour due to parking. The degree of saturation value reached 0.89 in conditions with parking and 0.68 without parking, indicating that road services are in categories E and C, respectively. The proposed solution is to provide a larger and more orderly special parking area, as well as strict regulation and supervision. Thus, it is expected that traffic flow on Jalan Somba Opu can increase, reduce congestion, and provide comfort for road users.